Politics, Liberal Idealism and Jewish Life in Nineteenth-Century Vienna: The Formative Years of Heinrich Jaques (1831–1894). (22nd August 2019) - Kwan, Jonathan
Abstract: This article addresses the formative years of the liberal parliamentarian Heinrich Jaques (1831–1894). It traces his family life, social world, education, professional career, and public activities prior to his election to parliament in 1879. The focus is on Jaques's personal perspective as he negotiated various events and influences. The article argues that the combined effects of the 1848–49 revolutions and an intense engagement with German humanist classics forged a strong loyalty and commitment to liberal values. This was manifested both in politics (as a belief in liberal reforms to Austria) and in everyday life (as guiding principles in daily conduct). For Jaques's generation in particular, the possibility of emancipation, integration, and acceptance was a goal to strive towards. Jaques pursued and articulated this vision in his writings and activities. His impressive achievements in the 1860s and 1870s are an example of the energy and hope of many Jews during the liberal era. For a number of reasons—economic downturn, widening democracy, a mobilized Catholic Church, resentment towards the liberal elites—antisemitism became an increasingly powerful factor in politics from the 1880s onwards. For Jaques and his fellow liberal Jews, the effect was profound. History and progress no longer seemed to be on the side of liberalism and Jewish integration. Nevertheless, for a certain milieu, the dreams of liberal humanism remained a strong and guiding presence in their lives.